Analisis Experiential Marketing Terhadap Customer Loyalty Melalui Customer Engagement Sebagai Variabel Mediasi - Siti Amanah; Kokom Komariah; R. Deni Muhammad Danial (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
ABSTRACT. This study aims to determine the description and influence of experiential marketing, customer engagement on customer loyalty in Oppo consumers. The research method used is a quantitative research research method with a causal descriptive approach. The objects in this study are experiential marketing, customer engagement, and customer loyalty. The population in this study were residents of the city of Sukabumi who made purchases on Oppo products. The sample used in this study amounted to 165 respondents who were taken based on Hair J theory which says that determining the number of samples depends on the number of indicators multiplied by 5 to 10. The sampling technique used is probability sampling technique, namely stratified random sampling. The data collection techniques used in this research are observation, interviews, literature study, documentation and questionnaire distribution. The data analysis technique used is Structural Equation Modeling (SEM) using partial least square (PLS). Keywords: Experiental Marketing; Customer Engagement; Customer Loyalty ABSTRAK. Penelitian ini bertujuan Untuk mengetahui gambaran dan pengaruh experiential marketing, customer engagement terhadap customer loyalty pada konsumen Oppo. Metode penelitian yang dilakukan adalah metode penelitian penelitian kuantitatif dengan pendekatan deskriptif kausal. Objek dalam penelitian ini adalah experiential marketing, customer engagement, dan customer loyalty. Populasi pada penelitian ini adalah warga kota sukabumi yang melakukan pembelian pada produk Oppo. Sampel yang digunakan pada penelitian ini berjumlah 165 responden yang diambil berdasarkan teori Hair J yang mengatakan bahwa menentukan jumlah sampel tergantung pada jumlah indikator yang dikali 5 hingga 10. Teknik sampling yang digunakan yaitu teknik probability sampling yaitu stratified random sampling. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah observasi, wawancara, studi pustaka, dokumentasi dan penyebaran kuisioner. Teknik analisa data yang digunakan yaitu Structural Equation Modeling (SEM) dengan menggunakan parsial least square (PLS) Kata Kunci : Experiental Marketing; Customer Engagement; Customer Loyalty